Avaliação da contaminação por mercúrio na foz do Rio Tapajós e exposição ambiental à população de Santarém-PA, Brasil - SOUSA, Enilson da Silva (Universidade Federal do Pará, 2018)
In the last decades of the twentieth century, academic work focused on discussion of the mercury problem in the Brazilian Amazon pointed to a mercury contamination of anthropogenic origin, especially from artisanal gold mining prospecting activities. In the mid-1990s and early years of this century, with the advancement of research in the field of geochemistry focused on this discussion, point to a possible geogenic origin of this contamination, and environmental exposure of the local population would be related to protein intake of animal origin, from the fish and work activities. The aim of this study is to analyze the speciation of Hg and methylmercury in soil and particulate matter in the mouth of the Tapajós River, and perception, mobilization capacity and political action on contamination by this metal of the population of Santarém; Elaborate mercury maps from spatially distributed data using up geostatistics to infer results for the location and risk of contamination of the metal along the mouth of the Tapajós River, Santarém-Pa.; and maps of contamination probability that this metal, which enabled the classification and quantification of contaminated areas for different confidence levels in and around the mouth of the Tapajós River; and quantify and evaluate the total mercury concentrations in water and particulate matter and hypotheses about the origin of this contamination in the Tapajos bay. The methodological procedures included the making location maps, georeferencing of points of collection and identification of the search area; Application Integrated Questionnaires for Measuring Social Capital Index - SC-IQ, proposed by the World Bank; Maps of the quantify the mercury concentrations in the study area and prepare maps of the spatial distribution of concentrations; and maps of the spatial distribution of concentrations and use of geostatistics (factorial kriging), which enabled the development of maps at different scales of variability associated with anthropogenic or geogenic origin activities. Two campaigns one in July and December 2014, with 37 and 45 sampling points in each were conducted. The results point to a possible contamination of the area at some points, with indexes to the top of the type recommended by the resolution n. 357/2005, of CONAMA. The results of the factorial kriging point to the possibility that mercury concentrations are associated with the natural environment itself, although it may have contributions due to human activity such as mining and industrial activities in the basin.